Indobuildtech Digital Fair Marketing Communication Planning (Marketing Communication Planning of Indobuildtech Digital Fair) - Dina Hardina Gultom; Jamalulail Jamalulail; Hayu Lusianawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze and identify how the planning of marketing communications for the Indobuildtech Digital Fair event as the first virtual exhibition in Indonesia in the category of building materials and interior exhibitions in 2020. In this study, PT Debindo International Trade and Exhibitions as the marketer of the IndoBuildTech Digital Fair event created an exchange of information. between the company and potential customers. So that researchers use communication theory to support the marketing communication planning model specifically for event services. In this study, researchers used descriptive qualitative research methods which were analyzed based on data that had been obtained through interviews with informants. The results showed that the marketing communication planning for the IndoBuildTech Digital Fair event carried out by PT Debindo International Trade and Exhibitions was through 7 elements of stages (1) situation analysis, (2) objective setting, (3) positioning and message development (positioning and message development), (4) methods and media (method and media), (5) budget (budgeting), (6) implementation (implementation), (7) evaluation of measurement and supervision (evaluation, measurement, controlling ), as well as one additional element of marketing communication planning as a research finding, namely information technology (information technology) through the virtu-ex platform as a forum for organizing virtual exhibitions.